TINJAUAN TERHADAP PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2012 TENTANG TINDAK PIDANA RINGAN DALAM PENERAPAN DI INDONESIA - Chandra Wihandaka (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractChanges in the Criminal Code have now been changed according to conditions and situations. As in Articles 364, 373, 379, 384, 407 paragraph (1) and 482 of the Criminal Code, it has been amended by Perpu No.16, 1960, and Perpu No. 18/1960. The Supreme Court issued PERMA No.2 of 2012 to adjust the limits of minor criminal offenses. Based on this background, there is the main problem, namely how to review the Supreme Court Regulation Number 2 of 2012 concerning Minor Crimes in Community Application. This paper discusses the application of the Supreme Court Regulation Number 2 of 2012 concerning Adjustment of the Limits of Minor Crimes in the Criminal Code and the Effectiveness of the Supreme Court Regulation Number 2 of 2012 concerning the Adjustment of Limits of Minor Crimes. This paper is useful in explaining the role of the PERMA in society and the value of the benefits achieved in its application. The method used in writing this thesis uses library research. The type of approach used in this research is the legislation approach (the statue approach) and the fact approach. The results of this thesis research are in the form of regulations and the application of PERMA No. 2 of 2012 to the Community With the increase of minor criminal cases in the Community, the form / form of benefit value is based on PERMA No. 2 of 2012 is considered less effective in the community because it can cause unrest and disturbance of public order and a lack of deterrent effects for the perpetrators. This thesis gives a suggestion to be affirmed in the penalties listed in the Criminal Code (KUHP) for criminal offenders. And Judges in deciding sentences for perpetrators of minor crimes need to explore the values contained in the community in order to create a deterrent effect for the perpetrators and to get the value of benefits for the application of the law.Keywords : Minor Crimes, Supreme Court Regulations, Deterrent Effe